Full Costing vs Traditional Costing Which One is Better For Manufacturing Company - Vania Sharon Ardelia Satmono; Sri Trisnaningsih; Raden Muhammad Syah Arief Atmaja Wijaya (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine and analyze the analysis of the calculation of cost of production using the full costing method in determining the selling price at PT. Sutrajaya Indahtama. This research uses a comparative descriptive method with a qualitative approach to compare the calculation of cost of goods produced between the traditional method and the full costing method at PT Sutrajaya Indahtama. Data were collected through interviews, observations, and documentation. The analysis was conducted by identifying cost components, calculating total production costs, and comparing the efficiency and profitability of each method through financial ratio analysis and operational cost efficiency. The results showed that the calculation of cost of goods manufactured (COGS) using the full costing method resulted in a higher figure than the traditional method used by PT Sutrajaya Indahtama. The traditional method does not reflect the total cost as a whole because it does not include all indirect cost components. The application of the full costing method provides a more accurate picture of production costs, increases cost efficiency from the previous 43%, and helps companies identify and control waste. In addition, this method contributes to the improvement of the company's profitability, by preventing hidden losses due to underpricing and increasing the Return on Assets value.